The Islamization in the Malay Archipelago: a Study of Azyumardi Azra's Thought - Muhammad Rakha Bimantara F. Saragih; Yusra Dewi Siregar (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2023)
Indonesia, with over 231 million Muslim people, is home to the world's largest Muslim population. However, the origins of Islam in Indonesia and the process of Islamization in the Archipelago are still highly debated topics among historians. Azyumardi Azra, a distinguished historian, and former UIN Syarif Hidayatullah Jakarta rector, has extensively researched Islamization in the Archipelago. This journal serves the purpose of delving into Azra's scholarly perspective, offering insights and analysis on the intricate process of Islamization within Indonesia. The present study adopts a literature review approach to comprehend and analyze Azra's writings. Azra postulates that the Islamic connections with the Archipelago can be traced back to Arab countries via trade routes, which were notably influenced by the triumphant spread of Islam into Persia and the Indian Subcontinent during the Umayyad dynasty (660-749H). In conclusion, Azra held a firm perspective regarding the significant Arab influence during the initial phases of Islamization in the Archipelago.